1
You visited us 1 times! Enjoying our articles? Unlock Full Access!
Question

# Solve the following equations using matrix inversion method: $2x-3y+6=0$ and $6x+y+8=0$.

Open in App
Solution

## Solve system of linear equations using matrix inversion method:Step 1: Find the corresponding matrix equation.The given equations are:$2x-3y+6=0⇒2x-3y=-6$$6x+y+8=0⇒6x+y=-8$The corresponding matrix equation is$\left[\begin{array}{cc}2& -3\\ 6& 1\end{array}\right]\left[\begin{array}{c}x\\ y\end{array}\right]=\left[\begin{array}{c}-6\\ -8\end{array}\right]$$⇒\mathrm{AX}=\mathrm{B}$ where $\mathrm{A}=\left[\begin{array}{cc}2& -3\\ 6& 1\end{array}\right]$, $\mathrm{X}=\left[\begin{array}{c}x\\ y\end{array}\right]$ and $\mathrm{B}=\left[\begin{array}{c}-6\\ -8\end{array}\right]$Pre multiply the above matrix equation by ${\mathrm{A}}^{-1}$ on both sides:$\begin{array}{rcl}{\mathrm{A}}^{-1}\left(\mathrm{AX}\right)& =& {\mathrm{A}}^{-1}\left(\mathrm{B}\right)\\ & ⇒& \left({\mathrm{A}}^{-1}\mathrm{A}\right)\mathrm{X}={\mathrm{A}}^{-1}\mathrm{B}\\ & ⇒& \mathrm{IX}={\mathrm{A}}^{-1}\mathrm{B}\\ & ⇒& \mathrm{X}={\mathrm{A}}^{-1}\mathrm{B}\end{array}$Step 2: Find the inverse of $\mathrm{A}$.$\mathrm{A}=\left[\begin{array}{cc}2& -3\\ 6& 1\end{array}\right]$Determinant of $\mathrm{A}$ is$\begin{array}{rcl}\left|\mathrm{A}\right|& =& 2\left(1\right)-6\left(-3\right)\\ & ⇒& \left|\mathrm{A}\right|=2+18\\ & ⇒& \left|\mathrm{A}\right|=20\end{array}$Adjoint of $\mathrm{A}=\mathrm{adj}\mathrm{A}=\left[\begin{array}{cc}1& 3\\ -6& 2\end{array}\right]$Therefore,$\begin{array}{rcl}{\mathrm{A}}^{-1}& =& \frac{1}{\left|\mathrm{A}\right|}\left(\mathrm{adj}\mathrm{A}\right)\\ & ⇒& {\mathrm{A}}^{-1}=\frac{1}{20}\left[\begin{array}{cc}1& 3\\ -6& 2\end{array}\right]\end{array}$Step 3: Substitute the value of ${\mathrm{A}}^{-1}$ in the equation $\begin{array}{rcl}\mathrm{X}& =& {\mathrm{A}}^{-1}\mathrm{B}\end{array}$ and solve.$\begin{array}{rcl}\mathrm{X}& =& \frac{1}{20}\left[\begin{array}{cc}1& 3\\ -6& 2\end{array}\right]\left[\begin{array}{c}-6\\ -8\end{array}\right]\\ & =& \frac{1}{20}\left[\begin{array}{c}1\left(-6\right)+3\left(-8\right)\\ \left(-6\right)\left(-6\right)+2\left(-8\right)\end{array}\right]\\ & & \\ & =& \frac{1}{20}\left[\begin{array}{c}-30\\ 20\end{array}\right]\\ & =& \left[\begin{array}{c}\frac{-30}{20}\\ \frac{20}{20}\end{array}\right]\\ & =& \left[\begin{array}{c}\frac{-3}{2}\\ 1\end{array}\right]\end{array}$Hence,$\begin{array}{rcl}\mathrm{X}& =& \left[\begin{array}{c}\frac{-3}{2}\\ 1\end{array}\right]\\ & ⇒& \left[\begin{array}{c}x\\ y\end{array}\right]=\left[\begin{array}{c}\frac{-3}{2}\\ 1\end{array}\right]\\ & ⇒& x=\frac{-3}{2},\mathrm{y}=1\end{array}$Hence, the solution of the equations $2x-3y+6=0$ and $6x+y+8=0$ is $x=\frac{-3}{2},y=1$.

Suggest Corrections
2
Join BYJU'S Learning Program
Related Videos
Finding Inverse Using Elementary Transformations
MATHEMATICS
Watch in App
Join BYJU'S Learning Program